Development processing of cassava into cassava flour and modified cassava flour in Lampung Province - Ratna Wylis; Joko Susilo Utomo; Robert Asnawi (Buletin Palawija, 2012)
Fresh cassava rots are perishableif not treated immediately after harvest,because it has high of water content (65%). Processingof cassava into intermediate product such as flourcan be developed in the producing areas, because itis easily practiced by farmers with simple equipment.Flour can be further processed into a variety of foodproducts. Cassava flour processing technology is animprovement of cassava flour processing. Currently,modified cassava flour processing technologyhas beendeveloped by adding a starter during fermentation/immersion. This resulted in better quality of theflour, such as whiter colour, reduced spesific aromaof cassava, and the increase in peak viscosity. It canbe used as a substitute of wheat flour, rice flour orglutinous rice flour about 15–30%, for as cakes,muffins, and noodles. Application cassava flour, bothmodification and without modification is prospectiveto be developed in term of supporting food diversificationprogram in Lampung Province as a centerof cassava production in Indonesi